The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1021/cm051866c
|View full text |Cite
|
Sign up to set email alerts
|

New Soft Chemical Routes to Ferroelectric SrBi2Ta2O9

Abstract: Ferroelectric ceramics of strontium bismuth tantalate, SrBi 2 Ta 2 O 9 (SBT), have been synthesized in pure layer-structured perovskite phase by two new soft chemical techniques, namely, a sol-gel process and a coprecipitation method. The sol-gel process utilizes ethylene glycol as solvent while the coprecipitation technique makes use of a poly(ethylene glycol) 200 (PEG) and methanol mixture as solvent. The microstructure and properties of the ceramics have been studied and discussed. The sol-gel-derived ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Ethylene glycol has been proved to be a very good solvent to prepare metal oxides (i.e. SrBi 2 Ta 2 O 9 [17] and Ba 0.5 Sr 0.5 TiO 3 [14]) because the presence of two terminal hydroxyl groups in the molecule makes it easy for ethylene glycol to readily keep heterometallic units during hydrolysis reaction. It is reported that the linearly structured molecule of ethylene glycol is favorable for obtaining stable sol and acts as the template for a dense and linearly aligned structure of the precursor molecules [14].…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene glycol has been proved to be a very good solvent to prepare metal oxides (i.e. SrBi 2 Ta 2 O 9 [17] and Ba 0.5 Sr 0.5 TiO 3 [14]) because the presence of two terminal hydroxyl groups in the molecule makes it easy for ethylene glycol to readily keep heterometallic units during hydrolysis reaction. It is reported that the linearly structured molecule of ethylene glycol is favorable for obtaining stable sol and acts as the template for a dense and linearly aligned structure of the precursor molecules [14].…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, the T C values for the same compounds were reported in [11] to be 425 and 400°C, respectively. The higher T C values found in our sol-gel processed ceramics are believed to result from a more stoichiometric composition of the samples which were treated and sintered at relatively low temperature, since it is well known that the loss of Bi-O species can lead to a lowering of T C [21]. From Fig.…”
Section: Dielectric Measurementsmentioning
confidence: 60%
“…In this paper, we report the synthesis of Bi 4 Ti 3 O 12 and Bi 4−x La x Ti 3 O 12 ceramics by an improved sol-gel method developed based on ethylene glycol following our recent work on the soft chemical synthesis of SBT ceramics [21]. Our main objective is to study the effect of sol-gel processing parameters and La-doping on the phase formation and dielectric properties of the BLT compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved to be an effective solvent for the synthesis of complex oxides such as (1-x)Pb(Mg 1/3 Nb 2/3 )O 3 -xPbTiO 3 , [19][20][21][22] and Sr 2 Bi 2 Ta 2 O 9 . 23 Furthermore, the fine precursor powder obtained after the pyrolysis process, which possesses a large specific surface area and high reactivity, is advantageous in producing high-density ceramics, which is also necessary for achieving enhanced properties. …”
Section: Materials Synthesismentioning
confidence: 99%